Analisis Minat Belajar Sejarah Siswa SMA Negeri 4 Padangsidimpuan - Insan Fahmi Siregar; Nurhamida Siregar; Kasmawati Kasmawati (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The purpose of this research is to find out the students' interest in studying history at SMA Negeri 4 Padangsimpuan. Through online learning, the problem of student interest in learning is a factor that determines the quality of student learning outcomes. This type of research is descriptive quantitative research, with data collection through a questionnaire of students' interest in learning history with a total of 60 students as respondents. The data obtained were analyzed using triangulation in which the percentage results were interpreted in the form of conclusions. The results of this study showed that students' interest in learning history through online learning showed that an average of 57.5% of students had an interest in learning history online and as many as 77.91% of students had an interest in learning face-to-face. This gives the meaning that students' interest in learning history is higher in face-to-face learning than online learning. Students' interest in studying history subjects face-to-face is more enthusiastic.